Concept of Criminal Responsibility for Work Group Errors in Procurement of Goods or Services - Supardin; Amiruddin; Lalu Parman, (International Journal of Scientific Research and Management (IJSRM), 2019)
The study aims to determine the concept of criminal liability for work group errors in the procurement of goods or services. This research is normative legal research. The Concept of Criminal Liability for Errors of the Working Group in the Procurement of Goods and Services, namely all acts or actions that are illegal That is, that actions or actions in the procurement of goods or services are not in accordance with the laws and regulations starting from the stage of carrying out the preparation and implementation of selection of providers, carrying out preparation and implementation of selection of providers for electronic catalogs, and determining the winner/provider for the selection method. What results in a loss of state loss is a criminal act as stipulated in the law on corruption, namely Article 2 or Article 3 of the Republic of Indonesia Law Number 20 of 2001 concerning the Eradication of Corruption Crime changes to the Republic of Indonesia Law Number 31 of 1999 concerning Eradication Corruption Crime.